Community Engagement in Corporate Social Responsibility (CSR) Policy Design and Implementation: A Case Study of Sanzule Community, Ghana, and ENI Exploration and Production Company Limited. - Arthur, Wilfred King Arthur (Journal of Social Development Studies, 2025)
This case study explores the role of community engagement in the design and implementation of Corporate Social Responsibility (CSR) policies in Sanzule, Ghana. Focusing on Eni Exploration and Production Limited, the study investigates community involvement, decision-making, and participation in CSR initiatives (Chambers, 1994; Cernea, 1997). Using a case study approach, data were collected through interviews, document analysis, and observations. The study involved 67 participants, including local leaders, company employees, and health professionals. Eni’s CSR initiatives prioritize free, prior, and informed community consultations, aligning with its sustainability values (Eni, 2011). Regular meetings and a community liaison officer overseeing local content help integrate community perspectives into policy development. Eni collaborates with government agencies for needs assessments and implementation, focusing on sectors like health and education (WHO, 2010). The Livelihood Restoration Plan allows beneficiaries flexibility in selecting economic activities. This study underscores the importance of ongoing dialogue and collaboration for effective CSR implementation.